FAKTOR-FAKTOR YANG MEMPENGARUHI TERHADAP GANGGUAN MENSTRUASI PADA MAHASISWI REGULER DI STIKES KESOSI JAKARTA - Anitha Anitha; Cornelius Tri Wibowo (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
Menstrual disorder is one complaint on today's teenagers. adolescent disorders associated with menstruation, irregular menstrual cycles, pain, bleeding time and a lot of time period, while the factors that can affect menstrual disorders, among others, stress, physical activity, age, weight, genetics and nutrition. This study aims to determine the relationship between the level of stress and physical activity levels with menstrual disorders in female students in STIKes KESOSI Jakarta. This study uses analytic survey with cross sectional study approach. This research was conducted at campus STIKes KESOSI Jakarta with a sample of the regular students as much as 80 respondents. Collecting data using questionnaire research instruments. Data analysis is univariate analysis in the form of a frequency distribution and bivariate analysis in the form of two different test proportions (chi-square). Of the 80 female students had an average stress as much as 64.7%, moderate physical activity as much as 95%, and the average student who has menstrual abnormalities in the amount of 78.8%. There was no significant relationship between stress factors and physical activity with menstrual disorders in female students in STIKes KESOSI Jakarta, because (p> 0.05), namely (p value = 0.371) and (p value = 0.458)